Chrono-pharmacology-based antiplatelet therapy for acute myocardial infarction: editorial - Tual-Chalot, Simon; Stellos, Konstantinos (European heart journal, 2022)
This editorial refers to ‘Circadian nuclear receptor Rev-erbα is expressed by platelets and potentiates platelet activation and thrombus formation’, by J. Shi et al., https://doi.org/10.1093/eurheartj/ehac109.Ischaemic heart disease remains the leading cause of morbidity and mortality worldwide. Its most serious manifestation is acute myocardial infarction (AMI), an acute thrombotic occlusion of a large epicardial coronary artery leading to myocardial ischaemia, necrosis, and ultimately heart failure. The increased activation of circulating platelets is associated with myocardial infarct size, indicating that platelet activation is a major determinant of disease prognosis.1 Platelets are mainly known for their role in thrombosis; however, they also significantly contribute to atherosclerotic plaque development and progression before and after the atherothrombotic events.2 Inhibition of platelet activation and aggregation is an ultimate therapeutic goal in patients with AMI. However, while substantial breakthroughs in antiplatelet therapy have been achieved, the underlying mechanisms of (residual) platelet activation in patients with AMI remain poorly understood.